2010
DOI: 10.1063/1.3448238
|View full text |Cite
|
Sign up to set email alerts
|

Optical evaluation of multichannel radiative transitions originating from G45/2 level of Sm3+ in heavy-metal-gallate glasses

Abstract: Energy transfer characteristics of silicate glass doped with Er3+, Tm3+, and Ho3+ for 2μm emission J. Appl. Phys. 114, 243501 (2013); 10.1063/1.4852535 1.8 μ m emission of highly thulium doped fluorophosphate glasses J. Appl. Phys. 108, 083504 (2010); 10.1063/1.3499283 Spectroscopic properties and Judd-Ofelt theory analysis of Dy 3 + doped oxyfluoride silicate glassConventional visible and novel infrared ͑IR͒ emissions of Sm 3+ in heavy-metal-gallate glasses ͑Li 2 O-K 2 O -BaO-PbO-Bi 2 O 3 -Ga 2 O 3 , LKBPBG f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…which is similar to the trend observed in PKBASm10 [22], PKBFASm10 [22] and LKBPBG [30] glasses. From Table 3, the O 4 parameter is found to be higher in the present glass compared to PKBFASm10 [22], PbO-PbF 2 [24], PPNSm10 [25], PbO-PbF 2 -B 2 O 3 [26], LBTAFSm10 [27], lead borate [29], LKBPBG [30], PbO-GeO 2 -TeO 2 [31] and CdO-Al 2 O 3 -SiO 2 [32] glasses. The higher magnitude of O 4 in the present glass suggests higher rigidity of the medium and higher covalence around the Sm 3 þ ions.…”
Section: Energy Level Analysis and Free-ion Parameterssupporting
confidence: 89%
See 1 more Smart Citation
“…which is similar to the trend observed in PKBASm10 [22], PKBFASm10 [22] and LKBPBG [30] glasses. From Table 3, the O 4 parameter is found to be higher in the present glass compared to PKBFASm10 [22], PbO-PbF 2 [24], PPNSm10 [25], PbO-PbF 2 -B 2 O 3 [26], LBTAFSm10 [27], lead borate [29], LKBPBG [30], PbO-GeO 2 -TeO 2 [31] and CdO-Al 2 O 3 -SiO 2 [32] glasses. The higher magnitude of O 4 in the present glass suggests higher rigidity of the medium and higher covalence around the Sm 3 þ ions.…”
Section: Energy Level Analysis and Free-ion Parameterssupporting
confidence: 89%
“…The small root-mean-square deviation (s rms ) value of 70.58 Â 10 À 6 obtained between the experimental and calculated oscillator strengths indicates the good fit between the two values. The evaluated phenomenological JO intensity parameters, O 2 , O 4 and O 6 , are presented in Table 3 along with those reported for Sm 3þ :glasses [21,22,[24][25][26][27][28][29][30][31][32]. From the JO intensity parameters, the radiative parameters such as radiative transition probabilities (A R ) and fluorescence branching ratios (b R ) for the 6 H 5/2 , 6 H 7/2 6 H 9/2 and 6 H 11/2 levels of Sm 3þ ions in the title glasses have been determined and are shown in Table 4.…”
Section: Optical Absorption Spectrum and Energy Level Analysismentioning
confidence: 99%
“…The decay of exited states in Sm 3+ involves different mechanisms depending on the matrix. Earlier studies on optical absorption, fluorescence and lifetime measurements of Sm 3+ ions in oxyfluoroborate and oxide glasses have indicated the quenching of the fluorescence of 4 G 5/2 level [24,25]; this is attributed to quadrupole-quadrupole interaction among the samarium ions. Similarly, a number of earlier studies on spectroscopic properties of Sm 3+ ions in different glass matrices have revealed that the fluorescence yield of this rare earth ion is strongly dependent on its environment inside the glass network [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 95%
“…This peak can be attributed to the transitions 4 F 3/2 ? 6 H 5/2 as it is a well-known fact that Sm 3+ has two more emitting levels, 4 F 3/2 and 4 G 7/2 besides 4 G 5/2 though they have comparatively smaller lifetime (stability) than 4 G 5/2 [50]. The integrated intensity { R I ð mÞdð mÞ} ratio among green, greenish yellow, reddish orange, red and near infrared bands achieved in this series is: 4:16:49:30:1.…”
Section: Excitation and Luminescence Spectramentioning
confidence: 99%